2017
DOI: 10.1159/000480536
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Disparities in Preterm Infant Mortality and Severe Morbidity: A Population-Based Study

Abstract: Background: Disparities exist in the rates of preterm birth and infant mortality across different racial/ethnic groups. However, only a few studies have examined the impact of race/ethnicity on the outcomes of premature infants. Objective: To report the rates of mortality and severe neonatal morbidity among multiple gestational age (GA) groups stratified by race/ethnicity. Methods: A retrospective cohort study utilizing linked birth certificate, hospital discharge, readmission, and death records up to 1 year o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 22 publications
3
57
0
3
Order By: Relevance
“…Some regions had multiple studies other areas had none. A total of eight studies were reported from the United States covering a number of states including: California, Texas, Atlanta, Connecticut, and New York (3,6,9,(27)(28)(29)(30)(31). Multiple studies were also reported from the Europe including Poland, Romania, Finland, Belgium, Sweden and Switzerland (12,13,28,(32)(33)(34).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some regions had multiple studies other areas had none. A total of eight studies were reported from the United States covering a number of states including: California, Texas, Atlanta, Connecticut, and New York (3,6,9,(27)(28)(29)(30)(31). Multiple studies were also reported from the Europe including Poland, Romania, Finland, Belgium, Sweden and Switzerland (12,13,28,(32)(33)(34).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The publication year of the studies ranged from 1988 to 2019, but the majority were carried out after 2000. Some of the studies focused on evaluating a certain exposure (7,9,33,37), however, the data presented in these papers were not limited to the exposure groups and data from the general population was extracted to compute the incidence ( (28). Upon retrograde calculation of the number of NEC cases and dividing them by a total number of NICU preterm babies the incidence of NEC was 9.1%.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…For weathering specifically, researchers often use white women in their twenties as the universal reference group, an approach that does not sufficiently account for the increased baseline risk of poor outcomes among black women at all ages, nor for the increasing risk of poor birth outcomes with advancing maternal age for all women. [25][26][27][28] Furthermore, age is frequently grouped into broad, uneven categories and fails to include women at the tails of the distribution (below 20 years or over 35 years), a particular shortcoming as childbearing patterns have shifted towards later initiation of births among US women. 29,30 In addition, many early studies included only limited adjustment for multiple confounders, especially maternal health conditions and measures of socio-economic status, which have demonstrated associations with poor birth outcomes.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Recent reports have investigated the relationship between race and BPD and respiratory outcomes following preterm birth. 7,8,[13][14][15][16][17] Implicit in many such investigations is the question as to whether genetic sequence differences between racial groups are responsible for differences in risk of diseases such as BPD.…”
Section: Geneticsmentioning
confidence: 99%